Approach to the Fifth Five Year Plan of Nagaland - Planning Commission (Planning Commission, 1972)
At its meeting in New Delhi on the 30th and 31st May. 1972, the National Development Council considered and endorsed the Planning Commission’s, paper entitled 'Towards an Approach to the Fifth Plan.’ What then decided was that the basic objective of the Fifth Plan would be to remove poverty to the extent possible and to reduce the existing imbalances and inequalities in the distribution of income and wealth. It was recognized that elimination of abject poverty cannot be attained by merely accelerating the rate of growth of the economy.
Government of Nagaland